Keratinocyte-specific deletion of the receptor RAGE modulates the kinetics of skin inflammation in vivo - Leibold, Julia; Riehl, Astrid; Hettinger, Jan; Durben, Michael; Heß, Jochen; Angel, Peter (The journal of investigative dermatology, 2013)
The receptor for advanced glycation end products (RAGE) is a pattern recognition receptor causally related to the pathogenesis of acute and chronic inflammation. In a mouse model of inflammation-driven skin carcinogenesis, RAGE deletion conferred protection from the development of skin tumors due to a severely impaired cutaneous inflammation. Although the impact of RAGE expression in immune cells was shown to be essential for the maintenance of a cutaneous inflammatory reaction, the role of RAGE in keratinocytes remained unsolved. Using mice harboring a keratinocyte-specific deletion of RAGE, we analyzed its role in the regulation of an acute inflammatory response that was induced by topical treatment of the back skin with the phorbol ester 12-O-tetradecanoyl-phorbol-13-acetate (TPA). We show that RAGE expression in cutaneous keratinocytes modulates the strength and kinetics of acute inflammation and supports the maintenance of epidermal keratinocyte activation. To address the underlying molecular mechanism, we isolated interfollicular epidermis by laser microdissection for gene expression analysis, and identified RAGE as a regulator in the temporal control of TPA-induced epidermal tumor necrosis factor alpha transcript levels. In summary, our data demonstrate that RAGE expression in keratinocytes is critically involved in the perpetuation of acute inflammation and support the central role of RAGE in paracrine communication between keratinocytes and stromal immune cells.